Bile Acids in Inflammatory Bowel Disease: From Pathophysiology to Treatment - Samantha H. Bai; Arun Chandnani; Siyan Cao (Biomedicines)
Inflammatory bowel disease (IBD) is a chronic condition that affects about 7 million people worldwide, and new therapies are needed. Understanding the complex roles that bile acids (BAs) play in IBD may lead to the development of novel IBD treatments independent of direct immunosuppression. This review discusses the latest discoveries in the roles BAs play in IBD pathogenesis and explores how these discoveries offer promising new therapeutic targets to treat IBD and improve patient outcomes. Several therapies discussed include specific BA receptor (BAR) agonists, dietary therapies, supplements, probiotics, and mesenchymal stem cell therapies that have all been shown to decrease IBD disease activity.